Solution Manual of Engineering Mathematics (module 5) - Tay, Choo Chuan; Sakidin, Hamzah; Ranom, Rahifa; Baharon, Mohd Rizuan; Jamaludin, Irma Wani (Penerbit Universiti, UTeM, 2008)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding.